An open database on inequality and polarization in length of life (1950-2021) - Vanesa Jordá; Miguel Ni\~no-Zarazúa; Mercedes Tejería (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Monitoring health is key for identifying priorities in public health planning and improving healthcare services. Life expectancy has conventionally been regarded as a valuable indicator to compare the health status of different populations. However, this measure is simply the mean of the distribution of the length of life and, as such, neglects individual disparities in health outcomes. Tracking the evolution of lifespan inequality is essential to promoting social justice and equity by identifying and addressing the root causes of these disparities. In this paper, we use life tables from the UN World Population Prospects to develop the most comprehensive database of lifespan inequality and polarization for 258 countries and areas for the period 1950- 2021. To help with the visualization and the use of these estimates, we have designed a userfriendly website that enables users to compute lifespan inequality for any group of countries of their choice. These extensive series on the distribution of lifespans provide access to crucial information for researchers, policy-makers, and the general public, thus representing a fundamental step towards a better understanding of health differences within and between nations.
Keywords: I14; 330; inequality; polarization; lifespan; life expectancy